Nd, Sr, and Pb isotopic evidence for diverse lithospheric mantle sources of East African Rift carbonatites - Kalt, Angelika; Hegner, Ernst; Satir, Muharrem (Tectonophysics, 1997)
Carbonatites may provide valuable information on mantle source compositions as their isotopic ratios are insensitive to crustal contamination. In order to place constraints on mantle sources, nineteen samples from three Miocene to Quaternary carbonatite areas in the East African Rift were analysed for their Sr, Nd, and Pb isotopic compositions. The samples from Kerimasi (northern Tanzania), Homa Mountain, and Wasaki Peninsula (both Lake Victoria, Kenya) as a whole show considerable variations in their isotope ratios (0.70327-0.70502 for 87Sr/86Sr, 0.51249-0.51283 for 143Nd 144Nd, 18.72-20.41 for 206Pb/204Pb, 15.52-15.78 for 207Pb/204Pb, and 39.22-40.47 for 208Pb/204Pb) that lie between the inferred compositions for HIMU (high 238U/204Pb mantle) and EM I (enriched mantle I) components in most isotope plots. The internal isotopic variations of the three carbonatite areas define distinct arrays and diverse trends in isotope diagrams. Although the isotope data define linear arrays in SrNd and PbPb diagrams, which suggest binary mixing between HIMU and EM I mantle components, neither the isotopic compositions of the carbonatites as a whole nor the compositional ranges for individual carbonatite occurrences can be explained by such a process. This clearly emerges from the absence of linear data trends in SrPb and NdPb isotope plots and from the lack of consistent endmember compositions. These features are also displayed by previously published isotope data for East African carbonatites. It is therefore suggested that carbonatite complexes within the East African Rift have isotopically distinct and small mantle sources that are probably not adequately described in terms of the mantle components defined for oceanic basalts. Most likely, these sources are located in a heterogeneous lithospheric mantle and were produced by enrichment and depletion processes at different times and degrees.